1976
DOI: 10.1128/jb.126.1.157-165.1976
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for diverse types of large plasmids in tumor-inducing strains of Agrobacterium

Abstract: Homology between the large plasmids of 15 pathogenic Agrobacterium strains isolated from various parts of the world has been measured and was found to vary over a wide range, from 3 to 100%. Two genetically distinct groups of plasmids can be identified: one closely related to the plasmid of A. tumefaciens A6, an octopine-utilizing strain, and the other closely related to the plasmid of A. tumefaciens C-58, a nopaline-utilizing strain. The plasmids of four Agrobacterium strains do not belong to either group. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(39 citation statements)
references
References 23 publications
0
39
0
Order By: Relevance
“…Although this result may be due to the small number of markers tested or to the restriction of incoming DNA, it may, on the other hand, reflect the degree to which the two strains have diverged. The latter hypothesis is supported by the results of solution hybridization experiments, which show that strain 15955 shares only 43% nucleotide sequence homology with strain NT1, a plasmidcured derivative of strain C58 (10). Thus, it may be that, whereas the overall genetic organizations of these strains are similar, nucleotide sequence divergence may have raised an expression or recombination barrier between the two.…”
Section: Istr-101 Rif-101mentioning
confidence: 95%
“…Although this result may be due to the small number of markers tested or to the restriction of incoming DNA, it may, on the other hand, reflect the degree to which the two strains have diverged. The latter hypothesis is supported by the results of solution hybridization experiments, which show that strain 15955 shares only 43% nucleotide sequence homology with strain NT1, a plasmidcured derivative of strain C58 (10). Thus, it may be that, whereas the overall genetic organizations of these strains are similar, nucleotide sequence divergence may have raised an expression or recombination barrier between the two.…”
Section: Istr-101 Rif-101mentioning
confidence: 95%
“…WR3095 harbors pPHIJI (Beringer et al, 1978; gentamicin resistance) a plasmid incompatible with the incoming pWR64 clones; recombinants that translocated border fragments from the shuttle vector to the Ti plasmid exhibited resistance to both gentamicin and carbenicillin. From each recombinant we isolated total A. tumefaciens DNA and confirmed the structure of each recombinant by Southern analysis (Gillen et al, 1981;Maniatis et al, 1982;Currier and Nester, 1976).…”
Section: Border Fragment Translocationsmentioning
confidence: 99%
“…Thimann & Sachs (1966) reported that application of exogenous kinetin to pea plants resulted in altered development similar to that observed in infected plants and, additionally, they provided evidence that culture medium of the pathogen contained cytokinins; they suggested that bacterial synthesis of cytokinins was responsible for disease symptoms. The frequency of plasmid-borne virulence factors in other phytopathogenic bacteria (Van Larebeke et al, 1974;Currier & Nester, 1976;Gross et al, 1979;Comai & Kosuge, 1980) prompted investigators to examine the association between plasmids, virulence, and cytokinin production in R. fascians. Murai et al (1980) reported that highly virulent isolates had a unique circular plasmid, and that culture medium of virulent isolates contained up to 10 times more isopentenyladenine and cis-zeatin than did that of an avirulent isolate.…”
Section: Introductionmentioning
confidence: 99%